Design and fabrication of hexagonal-nut sorting machine - Rafique, Asad (070520),2011 (Islamabad. Department of Mechatronics (Air University Main Campus), 2011)
Sorting is the process in which items are differentiated on the basis of size, shape and colour. Sorting is common and very important process in industry. Besides making the different production lines for different products companies design the production lines in such a way that different products can manufactured on the same production line and sort out according to our requirement. Some companies also manufactured different hexagonal nuts on the same production lines. So they need to sort out nuts. Hexagonal nuts are widely used in automotive industries, mechanical workshops and machine manufacturing industries. They often need to sort out nuts. Our objective is to sort out hexagonal nuts on the basis of their weight. We use load cell, stepper motor and servo motors in our project.
BEMTS